A cluster-based secured data transmission protocol for efficient data gathering in WSN. (2nd December 2019) - Sharmila, P.; Priyadharson, A. Selwin Mich
Nowadays, Wireless Sensor Networks (WSNs) are widely used in all surveillance and domestic applications. Secure data gathering is a major concern in WSN in the presence of intruders. In existing works, secured data transmission was achieved through symmetric or asymmetric cryptographic schemes. However, it has high overhead and less confidentiality. In the proposed research, Cluster-based Secured Data Transmission Protocol (CSDTP) is developed to provide efficient data gathering. This protocol contains three modules. In the first module, cluster-based secure routing is implemented by route request, route reply and route assign phase. In the second module, data transmission is initiated. High packet delivery is achieved during this module. In the third module, secure data gathering is implemented using symmetric key encryption and decryption algorithm. The results of the simulation show that the CSDTP provides high data gathering ratio, more packet delivery ratio, less end to end delay, high packet integrity ratio and less overhead than existing schemes.